2003
DOI: 10.1056/nejmoa022148
|View full text |Cite|
|
Sign up to set email alerts
|

Neoadjuvant Chemotherapy plus Cystectomy Compared with Cystectomy Alone for Locally Advanced Bladder Cancer

Abstract: As compared with radical cystectomy alone, the use of neoadjuvant methotrexate, vinblastine, doxorubicin, and cisplatin followed by radical cystectomy increases the likelihood of eliminating residual cancer in the cystectomy specimen and is associated with improved survival among patients with locally advanced bladder cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

52
1,706
12
54

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 2,376 publications
(1,824 citation statements)
references
References 17 publications
52
1,706
12
54
Order By: Relevance
“…Interestingly, this was also seen in the large prospective, randomized trial reported by Grossman et al, in which patients were randomized to radical cystectomy or three cycles of neoadjuvant chemotherapy. In this report, 26% of patients overall were pT0 at cystectomy, and there was no survival difference in patients rendered P0 by neoadjuvant chemotherapy (48 of 126 patients, 38%) versus those rendered P0 by TUR (18 of 121 patients, 15%) [13]. Thus, it appears that the biologic and prognostic significance of P0 state is independent of whether this was achieved by means of a surgeon's knife (TURBT) or a medical oncologist's chemotherapy.…”
Section: Discussionmentioning
confidence: 65%
“…Interestingly, this was also seen in the large prospective, randomized trial reported by Grossman et al, in which patients were randomized to radical cystectomy or three cycles of neoadjuvant chemotherapy. In this report, 26% of patients overall were pT0 at cystectomy, and there was no survival difference in patients rendered P0 by neoadjuvant chemotherapy (48 of 126 patients, 38%) versus those rendered P0 by TUR (18 of 121 patients, 15%) [13]. Thus, it appears that the biologic and prognostic significance of P0 state is independent of whether this was achieved by means of a surgeon's knife (TURBT) or a medical oncologist's chemotherapy.…”
Section: Discussionmentioning
confidence: 65%
“…Although it has not been formally established as a surrogate endpoint, the pCR rate has been correlated with overall survival in several analyses that included the specific definition of pCR rate used in the current study. 4,33 The pivotal trial comparing neoadjuvant MVAC followed by surgery versus surgery alone in patients with muscle-invasive bladder cancer (Southwest Oncology Group trial SWOG 8710) demonstrated that patients who had no residual disease at the time of surgery (pT0) had a markedly improved overall survival compared with those who had >pT0 disease (HR, 2.51; 95% CI, 1.47-4.27; P 5 .0008). 33 A correlation between the pCR rate and clinical outcomes also was demonstrated in previous analyses of neoadjuvant GC.…”
Section: Survivalmentioning
confidence: 99%
“…However, 2 large randomized trials have demonstrated an improvement in survival with the integration of neoadjuvant cisplatin-based combination chemotherapy, leading to the adoption of this approach as a treatment standard. 4,5 Despite the survival improvement established in randomized trials with the use of neoadjuvant methotrexate, vinblastine, doxorubicin, plus cisplatin (MVAC) or cisplatin, methotrexate, plus vinblastine 5 (CMV), concerns regarding the balance between the toxicity and efficacy of these regimens has contributed, at least in part, to the poor uptake of neoadjuvant chemotherapy. [4][5][6] In 2000, the results from a randomized phase 3 trial were published comparing gemcitabine plus cisplatin (GC) with standard MVAC in patients with metastatic bladder cancer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 The cooperative group mechanism assures a high level of participation by diverse community and academic hospitals, permitting analysis of possible variations in the pathologic examination of radical cystectomy specimens as practiced currently in the United States. In the current study, we assessed the quality of the pathologic evaluation of patients who were enrolled in the SWOG 8710 trial to determine whether current practices conform to suggested guidelines for reporting radical cystectomy specimens.…”
mentioning
confidence: 99%